2009
DOI: 10.1128/jcm.00997-08
|View full text |Cite
|
Sign up to set email alerts
|

Orientia tsutsugamushiBacteremia and Cytokine Levels in Vietnamese Scrub Typhus Patients

Abstract: Scrub typhus, caused by the intracellular bacterium Orientia tsutsugamushi, is a major cause of febrile illness in the Asia/Pacific region. Here, we implemented a novel real-time PCR and determined the relation of DNA target gene concentration with serum cytokine levels. The limit of detection of the novel real-time PCR was 1,062 DNA copies per ml of EDTA whole blood. Specificity was excellent as determined on a panel of blood-and skin-borne bacteria, including Rickettsia spp. as well as healthy Vietnamese blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 14 publications
7
44
0
Order By: Relevance
“…For qPCR-based quantification of O. tsutsugamushi , the majority of methods are based on the quantification of single copy genes that often yield high cycle threshold (Ct) values and low bacterial copy numbers, thus compromising statistical analyses [9], [20], [24], [25].…”
Section: Resultsmentioning
confidence: 99%
“…For qPCR-based quantification of O. tsutsugamushi , the majority of methods are based on the quantification of single copy genes that often yield high cycle threshold (Ct) values and low bacterial copy numbers, thus compromising statistical analyses [9], [20], [24], [25].…”
Section: Resultsmentioning
confidence: 99%
“…We estimate that hypercytokinemia may contribute to the disease severity of rickettsiosis, including JSF. For instance, fulminant TD has been associated with hemophagocytic syndrome (10), and this syndrome may represent a hyperreaction of the immune system mediated by an overactivated cytokine network during the advanced stages of rickettsial infection (19,(26)(27)(28). We previously reported that a downregulation of these cytokines and chemokines is observed after the administration of tetracyclines, demonstrated a correlation between the severity of TD and the serum concentration of TNF-␣ in the acute phase of the disease, and showed that TNF-␣ levels are predictive of the severity of TD (18,19,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…[87][88][89][90][91][92] However, mechanistic studies of protective or deleterious effects of these molecules have not been pursued. Indeed, the roles of CD4 and CD8 T lymphocytes, natural killer (NK) cells, NKT cells, dendritic cells, macrophages, and endothelial cells have not been evaluated in animal models with disseminated endothelial infection that appropriately represents scrub typhus (Table 4).…”
mentioning
confidence: 99%